Pengaruh 5 Varietas Ubi Jalar Terhadap Produksi Ubi Jalar (Ipomea Batatas L) di Lahan Bpp Lampung - Hasan Basri (Balitbangda Provinsi Lampung, 2018)
Differential (BNT) test at 5% level. The results of the study The growth of several varieties of sweet potatoes showed that there is very useful for the location in the field of farming BPP Lampung is shown with good and healthy tendrils growth and good production. The results of his study showed that the highest production in Ayammurasaki (B) varieties = 20.24 kg / 10 m2 was equivalent to 20.24 tons per hectare, the second highest Sawentar (C) 18.46 kg / 10 m2 was equivalent to 18.46 tons per hectare, then Sukuh (A) = 17.20 kg / 10 m2 is equivalent to 17.20 tons per hectare and the second lowest varieties of Antin-1 (E) = 12.02 kg / 10 m2 is equivalent to 12.02 tons per hectares and the lowest production is Cangkuang (D) = 8.00 kg / 10 m2 equivalent to 8.00 tons per hectare.